Emergency Notification And Healthcare Mobile Application For Elderly - Ma, Xin Ying; Hafit, Hanayanti (Applied Information Technology And Computer Science, 2022)
In Malaysia, 15 percent of Malaysians are expected to become aged 65 years old and older in the year 2030 and about seven percent of Malaysia's population 60 years and older are living alone. However, it will be serious if the elderly living alone suffers emergence health problems or an emergency happens. Therefore, emergency notification and healthcare mobile application is developed to help the elderly to notify their guardians in a faster and easier way when they meet emergencies as well as to provide healthcare service to the elderly. The methodology used in this project is iterative and incremental development model. This application is developed using Android Studio and Firebase as database storage. Overall, this mobile application is designed to provide emergency and healthcare supports that give advantages to the elderly and their guardians.